The Impact of Word of Mouth on Customer Satisfaction: An Empirical Study at a Music Tea Room in Ho Chi Minh City, Vietnam - Nguyen, Ky; Nguyen, Hong Ha; Bui, Van Thoi; Nguyen, Phu My Linh (Migration Letters, 2024)
Purpose: This paper investigates both the direct impact and indirect impact of word of mouth on intention to return to tea rooms in Ho Chi Minh City – Vietnam. Design/Methodology/Approach: direct impact of Word of mouth on intention to return to tea rooms and indirect impact of word of mouth on intention to return to tea rooms via mediating role of customer satisfaction, confirmed by 277 customers who come directly to Music Tea Rooms in Ho Chi Minh City – Vietnam and applying confirmatory factor analysis (CFA) and linear structural (SEM) models to test the hypotheses. Findings: The result shows that direct impact and indirect impact of word of mouth on intention to return to tea rooms via mediating role of customer satisfaction Conclusion: Intention to return to tea rooms are directly and indirectly impacted by word of mouth via mediating role of customer satisfaction Practical Implications: The paper’s investigation has implications for managers who run directly the tea rooms in Ho Chi Minh City – Vietnam where to build performance oriented strategics. Limitations: this paper has been only tested in Ho Chi Minh City - Vietnam; therefore, there could evaluations generalization in research scope.